2022
DOI: 10.1002/jhet.4498
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of new thiazine and thiazole derivatives via cyclization reactions; investigating their electronic properties and determination of antioxidant properties

Abstract: 4-[2,4-dimethoxyphenyl]-6-phenyl-2-thioxo-1,2,3,4-tetrahydropyrimidin-5-yl) (phenyl) methanone (1) have been prepared by Biginelli three-component cyclocondensation reaction of catalyzed with p-toluene sulfonic acid in ethanol. Pyrimido[2,1-b]thiazine (2) and thiazolo[3,2-a]pyrimidine (3) derivatives were obtained by a simple one-pot condensation reaction of starting compound 1 and 3-bromopropionic acid, bromoacetic acid and, respectively. By performing the reactions of compound 3 with heteroaromatic and aroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The % inhibition of 77 was 91.3 with respect to standard vitamin C. Ergan et al found the antioxidant property of one of the compounds 78 using the DPPH method [52]. This thioxopyrimidine compound exhibited the highest effectiveness among all the tested compounds; the inhibitory effect was 27%.…”
Section: Biological Applications Of Pyrimidine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…The % inhibition of 77 was 91.3 with respect to standard vitamin C. Ergan et al found the antioxidant property of one of the compounds 78 using the DPPH method [52]. This thioxopyrimidine compound exhibited the highest effectiveness among all the tested compounds; the inhibitory effect was 27%.…”
Section: Biological Applications Of Pyrimidine Derivativesmentioning
confidence: 99%
“…These interactions are essential for the proper functioning of nucleic acids, the transmission of genetic information, and a wide range of other cellular processes (Figure 3) [46]. Additionally, pyrimidine derivatives have a wide range of biological properties in the therapeutic industry, including antimicrobial [47], antibacterial [48], antifungal [49], anti‐inflammatory [50], antitumor [8], anticancer [51], antioxidant [52], antihypertension [53], anti‐HIV [54], antimalarial [55], antiviral [56], insecticide [57], antiplasmodial [58] activities.…”
Section: Introductionmentioning
confidence: 99%
“…Highly functionalized 2-imino-1,3-thiazinones are ubiquitous subunits that are widely present in a vast array of natural products and biologically active molecules. 1 As exemplified in Scheme 1, BTZ043 and its closest congener PBTZ169 have been found to be anti-tuberculosis agents. 2 Compound I displays significant antifungal activity against Aspergillus niger and Fusarium oxysporum.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the thiazole molecules also showed inhibition against SARS-CoV-2 virus disease 14,15 . Several procedures for synthesizing thiazole derivatives are described in the literature [16][17][18][19][20][21][22][23] .…”
mentioning
confidence: 99%